Meta-Analysis of Astragalus-Containing Traditional Chinese Medicine Combined With Chemotherapy for Colorectal Cancer: Efficacy and Safety to Tumor Response - Lin, Shuang; An, Xiaoxia; Guo, Yong; Gu, Jianzhong; Xie, Tian; Wu, Qibiao; Sui, Xinbing (Frontiers in Oncology, 2019)
This meta-analysis evaluated the comparative efficacy and safety for the addition of Astragalus-based Chinese medicines combined with chemotherapy and chemotherapy alone for the treatment of colorectal cancer. Systematic literature searches were applied to Pubmed, Embase, Cochrane Library, Ovid, Web of Science, China Academic Journals (CNKI), Chinese Science and Technology Journals (CQVIP) and Chinese Biomedical Literature databases. Twenty-two studies matched the selection criteria, which reported on 1409 subjects. This meta-analysis indicated that Astragalus-based Chinese medicines combined with chemotherapy in the treatment of colorectal cancer may increase the efficiency of tumor response rate (RR: 1.52; 95% CI: 1.24 to 1.87; p < 0.0001), improve their life quality based on KPS (RR: 2.51; 95% CI: 1.85 to 3.42; p < 0.00001 and WMD: 10.96; 95% CI: 9.45 to 12.47; p < 0.00001), and reduce the adverse reactions, including neutropenia (RR: 0.52; 95% CI: 0.44 to 0.62; p < 0.00001), anemia (RR: 0.49; 95% CI: 0.34 to 0.70; p < 0.0001), thrombocytopenia (RR: 0.59; 95% CI: 0.46 to 0.77; p = 0.0001), nausea and vomiting (RR: 0.56; 95% CI: 0.46 to 0.68; p < 0.00001), diarrhea (RR: 0.55; 95% CI: 0.40 to 0.75; p = 0.0001), and neurotoxicity (RR: 0.56; 95% CI: 0.49 to 0.65; p < 0.00001). Hepatic dysfunction (RR: 0.76; 95% CI: 0.53 to 1.09; p = 0.13) and renal dysfunction (RR: 0.95; 95% CI: 0.51 to 1.76; p =0.87) were similar between two groups. The results showed that Astragalus-based Chinese medicines combined with chemotherapy in the treatment of colorectal cancer may increase the efficiency of TRR, improve their life quality, and reduce the adverse reactions that result from chemotherapy when compared with chemotherapy alone. However, the long-term, high-quality researches with a large sample size in different populations are required to further verify the above conclusions.